1998
DOI: 10.1042/cs0950241
|View full text |Cite
|
Sign up to set email alerts
|

A central γ-aminobutyric acid mechanism in cardiac vagal control in man revealed by studies with intravenous midazolam

Abstract: 1. Animal studies show that cardiac vagal tone can be modified by gamma-aminobutyric acid neurons acting at several sites in the central nervous system. The present study has attempted to determine whether similar control exists in humans by using midazolam, a benzodiazepine. Benzodiazepines exert their main actions on the central nervous system by interacting co-operatively at the gamma-aminobutyric acid receptor. 2. Twenty patients took part in the study before undergoing cardiac catheterization. After resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
(28 reference statements)
2
11
0
Order By: Relevance
“…Previously we have shown that there is a GABA A -mediated suppression of cardiac vagal tone in man [9][10][11], which is in agreement with existing animal data [13,21]. In the present study it was found that resting cardiac vagal tone was little affected by 10 mg oral diazepam,as has been noted previously [25], unlike the dramatic reductions seen with the more potent benzodiazepine midazolam [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previously we have shown that there is a GABA A -mediated suppression of cardiac vagal tone in man [9][10][11], which is in agreement with existing animal data [13,21]. In the present study it was found that resting cardiac vagal tone was little affected by 10 mg oral diazepam,as has been noted previously [25], unlike the dramatic reductions seen with the more potent benzodiazepine midazolam [11].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study it was found that resting cardiac vagal tone was little affected by 10 mg oral diazepam,as has been noted previously [25], unlike the dramatic reductions seen with the more potent benzodiazepine midazolam [11]. The results of time-and frequency-domain analysis also show no significant differences between diazepam and placebo.…”
Section: Discussionsupporting
confidence: 83%
“…It is well known that the activity of the HPA system is inhibited by GABAergic mechanisms (Holsboer 1998). In contrast, heart rate has been shown to increase following treatment with benzodiazepines in rats (Castro et al 1999) and humans (Farmer et al 1998) which is in line with the differential effects of vigabatrin on HPA system activity and heart rate.…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that midazolam decreased both LF and HF in HRV without changes in LF/HF ratio [12] and depressed sympathetic activity to produce a vagotonic condition during spinal anesthesia [2]. The effects of benzodiazepine may be mediated by the modulation of GABAergic tone in the brain stem [13], which is involved in the endogenous regulation of SAP and vagal outflow to the heart and respiratory tract [14]. In this study, the HF component in HRV and SAPV with midazolam or propofol was thought to be secondary to the activities of the coupled cardiorespiratory neurons and ventilatory periodicity.…”
Section: Discussionmentioning
confidence: 99%